2020
DOI: 10.3390/s20226637
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Wearable Devices with Biofeedback on Biomechanical Performance of Running—A Systematic Review

Abstract: This present review includes a systematic search for peer-reviewed articles published between March 2009 and March 2020 that evaluated the effects of wearable devices with biofeedback on the biomechanics of running. The included articles did not focus on physiological and metabolic metrics. Articles with patients, animals, orthoses, exoskeletons and virtual reality were not included. Following the PRISMA guidelines, 417 articles were first identified, and nineteen were selected following the removal of duplica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 94 publications
(488 reference statements)
0
13
0
Order By: Relevance
“…Another found that feedback from a computer mouse caused workers to modify their postures, which resulted in the reduction of neck and/or shoulder WMSD in workers [ 147 ]. In the majority of reviews, the authors appeal for higher-quality studies investigating WIST feedback [ 44 , 146 , 148 ]. Thus, improving the quality of future studies may enable the greater utility of WIST in rehabilitation, clinical and workplace settings.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Another found that feedback from a computer mouse caused workers to modify their postures, which resulted in the reduction of neck and/or shoulder WMSD in workers [ 147 ]. In the majority of reviews, the authors appeal for higher-quality studies investigating WIST feedback [ 44 , 146 , 148 ]. Thus, improving the quality of future studies may enable the greater utility of WIST in rehabilitation, clinical and workplace settings.…”
Section: Discussionmentioning
confidence: 99%
“…In other sectors of health research, the retention of learned movement behaviour from WIST was shown for arm-hand movement in stroke rehabilitation [ 43 , 150 ] and lower limb running biomechanics [ 44 ]. Previous research on the retention of skills following feedback has indicated that a fading schedule of feedback is most effective for motor-relearning and for learned skills to be retained, suggesting that gradually reducing the dependence on external feedback improved the intrinsic feedback mechanisms and subsequent motor re-learning to occur [ 44 , 132 , 151 ]. Though, the retention of skills following feedback is seldom evaluated [ 146 ]; hence, further post-evaluation research is required.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The available data, in a broad sense, makes sports technology a helpful and effective companion in improving performance and physical condition [ 7 ], enhancing motivation [ 8 ] and preventing injuries [ 9 , 10 ]. There has been a recent focus on measuring and improving running technique through technology, as technique is an essential determinant of running performance and running-related injuries [ 3 ].…”
Section: Introductionmentioning
confidence: 99%